Nutrition in Interwar Britain: A Possible Resolution of the Healthy or Hungry 1930s Debate? - Ian Gazeley; Andrew T. Newell; Kevin Reynolds; Hector Gutierrez Rufrancos (Institute of Labor Economics (IZA), 2018)
This paper re-examines energy and nutritional available to British working-class households in the 1930s using the individual household expenditure and consumption data derived from the 1937/8 Ministry of Labour household expenditure survey and the 1938/9 individual dietary data collected by the Rowett Research Institute. We conclude that for working households, energy and nutritional availability improved significantly compared with current estimates of availability before the First World War. For unemployed headed households, and female headed households in employment, the situation was much worse with energy and nutritional availability at similar levels to households that would be described as destitute at the turn of the Twentieth Century. Finally, we examine the impact of state interventions to improve diet and nutrition and conclude that these made a difference, but other than the case of calcium, they did not represent a decisive intervention, as many households in receipt of free school meals and milk did not have sufficient nutrients available in their diets to meet modern dietary standards.
Keywords: I30; N34; 330; nutrition; Britain; 1930s; working class